HUBUNGAN ANTARA ACADEMIC SELF-EFFICACY DENGAN CAREER ADAPTABILITY PADA MAHASISWA TINGKAT AKHIR DI JAKARTA - Jessica, Joanna; Kembaren, Esther Muliana (Atma Jaya Catholic University of Indonesia, 2024)
One of the major problems in Indonesia is the high unemployment rate, including among undergraduates. In 2023, the undergraduate unemployment rate was approximately 958,000, or 12% of the total rate. Several factors affect an individual's ability to get a job. One of them is career adaptability, the process of achieving career goals that needs to be developed since undergoing education, especially in final-year students. However, little effort has been made to improve students' career adaptability, such as academic self-efficacy. The purpose of this study is to examine the relationship between academic self-efficacy and career adaptability in final-year students in Jakarta. A correlational quantitative method was applied to 121 final-year students in Jakarta obtained through convenience sampling techniques. The measuring tool used to measure academic self-efficacy is The Academic Self-Efficacy Scale (TASES) which has gone through a validity test with a corrected-item total correlation score in the range of .384-.602 and Cronbach's alpha reliability score of .885. Meanwhile, the measuring tool for career adaptability is the Career Adapt-Abilities Scale (CAAS) with validity test results in the range of .322-.652 and a reliability score of .905. Based on the results of the correlation test with Spearman's correlation, there was a significant positive relationship between academic self-efficacy and career adaptability in final-year students in Jakarta, with a Spearman's Rho score of .636, p-value < .01. It can be concluded that the higher the academic self-efficacy, the higher the career adaptability of final-year students. Self-confidence in academic ability helps individuals prepare for future careers.